1989
DOI: 10.3354/dao007159
|View full text |Cite
|
Sign up to set email alerts
|

Metastasizing adenocarcinoma of the stomach in a harbor porpoise, Phocoena phocoena

Abstract: The first case of a metastasizing hlstologically malignant tumor with fatal outcome in a harbor porpoise Phocoena phocoena is described. According to the World Health Organization (WHO) classification of tumors in domestic animals, thls neoplasm represents a well differentiated scirrhous tubular adenocarcinoma of the stomach, metastasizing by way of veins, lymphatics and by implantation in the peritonea1 cavity, uterus, lymph nodes, and liver The possible significance of environmental carcinogenic agents being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Adenocarcinoma of the gastrointestinal tract is the most frequent cancer observed in SLE beluga (11 cases or 7 % of mature adults examined). In contrast, only three cases of gastrointestinal epithelial cancers have been reported in other populations of cetaceans worldwide, and two of these were gastric adenocarcinomas in harbor porpoises, both from the North Sea [Breuer et al,1989; Parsons and Jefferson, 2000; Siebert et al, 2010]. Mammary cancer, which has not been reported elsewhere in cetaceans, is second to gastrointestinal tract cancer in SLE belugas, affecting 8 (or 9.9%) of mature adult females examined [Lair et al, 2016].…”
Section: Introductionmentioning
confidence: 99%
“…Adenocarcinoma of the gastrointestinal tract is the most frequent cancer observed in SLE beluga (11 cases or 7 % of mature adults examined). In contrast, only three cases of gastrointestinal epithelial cancers have been reported in other populations of cetaceans worldwide, and two of these were gastric adenocarcinomas in harbor porpoises, both from the North Sea [Breuer et al,1989; Parsons and Jefferson, 2000; Siebert et al, 2010]. Mammary cancer, which has not been reported elsewhere in cetaceans, is second to gastrointestinal tract cancer in SLE belugas, affecting 8 (or 9.9%) of mature adult females examined [Lair et al, 2016].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, stomach tumours have been reported in harbor porpoise (Phocoena phocoena), blue shark (Prionace glauca) and Asian sea bass (Lates calcarifer) [11][12][13]19]. Gopalakrishnan et al has reported skin tumour (0.38%) in S. longiceps, Parangipettai coastal waters [2].…”
Section: Discussionmentioning
confidence: 99%
“…But gastric tumour related reports are meager, such as harbor porpoise, blue shark and sea bass [11][12][13]. The Indian oil sardine [Sardinella longiceps (S. longiceps)] is distributed abundantly along the east and west coasts of India [14].…”
Section: Introductionmentioning
confidence: 99%
“…Systematic pathological investigations have been performed on harbour porpoises Phocoena phocoena from several different regions (Baker & Martin 1992, Siebert et al 2001, Jauniaux et al 2002, Jepson et al 2005), but only a few neoplastic diseases are reported, including a cutaneous squamous papilloma (Geraci et al 1987), one gastric adenocarcinoma with multiple metastases (Breuer et al 1989), one adenocarcinoma involving the posterior abdominal tissues with large numbers of secondary tumours on the sero sal surface (Baker & Martin 1992), an adrenal papilloma (Newman & Smith 2006) and a gastric squamous cell carcinoma (Siebert et al 2010). In this paper the morphological findings of an ovarian granulosa cell tumour in a harbour porpoise are described.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Besides granulosa cells, theca or luteinised cells and fibroblasts are found. Granulosa cell tumours have been described in a fin whale Balaenoptera physalus, a blue whale B. musculus, a short-finned pilot whale Globicephala macro rhynchus, beluga whales Delphinapterus leucas, a California sea lion Zalaphus californianus, a fur seal Callorhinis ursinis and a cape fur seal Arctocephalus pusillus (Rewell & Willis 1949, Landy 1980, Howard et al 1983, Benirschke & Marsh 1984, Martineau et al 1988, De Guise et al 1994.Systematic pathological investigations have been performed on harbour porpoises Phocoena phocoena from several different regions (Baker & Martin 1992, Siebert et al 2001, Jauniaux et al 2002, Jepson et al 2005), but only a few neoplastic diseases are reported, including a cutaneous squamous papilloma (Geraci et al 1987), one gastric adenocarcinoma with multiple metastases (Breuer et al 1989), one adenocarcinoma involving the posterior abdominal tissues with large numbers of secondary tumours on the sero sal surface (Baker & Martin 1992), an adrenal papilloma (Newman & Smith 2006) and a gastric squamous cell carcinoma (Siebert et al 2010). In this paper the morphological findings of an ovarian granulosa cell tumour in a harbour porpoise are described.…”
mentioning
confidence: 99%